2000
DOI: 10.1016/s1010-7940(00)00592-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined photodynamic therapy and hyperbaric oxygenation in carcinoma of the esophagus and the esophago-gastric junction✩

Abstract: According to this prospective non-randomized study, combined PDT/HBO represents a new approach in the treatment of esophageal and cardia cancer which appears to have enhanced the efficiency of PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…Meta-analysis was not possible due to heterogeneity between the trials. All trials reported morbidity results, seven reported on mortality [113][114][115][116][117][118][119] and four reported on QoL outcomes. [115][116][117][118] Only two of the studies reported resource use, both in terms of days of hospitalisation.…”
Section: Results Of Effectiveness (Palliative Intent)mentioning
confidence: 99%
See 4 more Smart Citations
“…Meta-analysis was not possible due to heterogeneity between the trials. All trials reported morbidity results, seven reported on mortality [113][114][115][116][117][118][119] and four reported on QoL outcomes. [115][116][117][118] Only two of the studies reported resource use, both in terms of days of hospitalisation.…”
Section: Results Of Effectiveness (Palliative Intent)mentioning
confidence: 99%
“…115,116 The comparison of HpD and ALA found no significant differences in Karnofsky status scores (44% vs 23%, p = 0.12).…”
Section: Quality Of Lifementioning
confidence: 90%
See 3 more Smart Citations